Nutrient Budgeting, Economics and Energetics of Cowpea under Potassium and Phosphorus Management (SAARC Journal of Agriculture, 2014)
Low availability of phosphorus (P) and potassium (K) in acidic soil is a major constraint for crop production. Cowpea was grown under split-plot design with three levels of K and P (viz., 100%, 75% and 50% of recommended dose). Green pod and stover yield was 20.9 and 16.9% higher with 100% K over 50% K application. Similarly, 100% P had 20.2% higher green pod and 16.6% higher stover yield over 50% P. Production efficiency was found higher with 100% K and P (48.6 and 49.0 kg ha-1 day-1 respectively) followed by 75% K. The actual gain of N, P and K, and balance were higher with the increase of K and P levels but reverse in case of gross and net return, and BCR. The energy productivity and energy use efficiency were higher on 100% K and P. Cowpea on acid soil along with 100% recommended dose of 40 kg K and 60 kg P ha-1 showed highest yield along with soil fertility restoration as well as reduced the cost of inorganic fertilizer, higher BCR (1.89) and energy requirement. DOI: http://dx.doi.org/10.3329/sja.v11i2.18408 SAARC J. Agri., 11(2): 129-140(2013)